2019
DOI: 10.3389/fphar.2019.01178
|View full text |Cite
|
Sign up to set email alerts
|

Piperlongumine Inhibits Akt Phosphorylation to Reverse Resistance to Cisplatin in Human Non-Small Cell Lung Cancer Cells via ROS Regulation

Abstract: Resistance is a major concern when administering chemotherapy to patients with non-small cell lung cancer (NSCLC). Chemosensitizer are agents that can reverse resistance to chemotherapeutic drugs, thereby enhancing the chemosensitivity of tumor cells. Thus, their development will improve therapeutic efficacy in cancer. However, few effective chemosensitizer have been identified to date. Piperlongumine (PL) has been shown to effectively reverse resistance to chemotherapeutic drugs in several types of cancers. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…In line with our data, PIP has been found to reverse chemotherapy resistance in several cancers [60][61][62][63]. Interestingly, a recent study showed PIP to reverse resistance to cisplatin in non-small cell lung cancer cells by inhibiting AKT phosphorylation [64].…”
Section: Discussionsupporting
confidence: 90%
“…In line with our data, PIP has been found to reverse chemotherapy resistance in several cancers [60][61][62][63]. Interestingly, a recent study showed PIP to reverse resistance to cisplatin in non-small cell lung cancer cells by inhibiting AKT phosphorylation [64].…”
Section: Discussionsupporting
confidence: 90%
“…Various doses and values of the IC 50 of the selected alkaloids have been reported in the literature. In the studies provided by Zheng et al and Zhang et al on two types of lung cancer cell lines (A549 and NCI-H460), it was shown that the IC 50 for PL ranged from 13 to 15 µM [36,37]. Similar results were obtained by Wang et al, who confirmed a high cytotoxicity and dose-dependent reduction of A549 survival following a treatment with PL [38].…”
Section: Discussionsupporting
confidence: 65%
“…29 PL enhanced the tumor-killing effect of traditional chemotherapy and radiotherapy and overcomes drug resistance in human cancer cells. 30,31 Although treatment with PL resulted in cell cycle arrest, the mechanism underlying such a role of PL in CRC cells remains elusive. In the present study, we found that PL dose-dependently suppressed the expression of Cyclin D1 and caused cell cycle G0/G1 arrest in CRC cells.…”
Section: Discussionmentioning
confidence: 99%